Refleksi Moral Diri Dalam Manaqib Islam (Kajian Historis Kitab Manaqib al-Busyra Karya Sayyid Muhammad ibn Alawi al-Maliki) - Syamsuri Ali (Departement of Mathematics Education, 2023)
The Islamic tradition which is rooted in the culture of society in Indonesia has diversity. Traditions can also be found in art forms and religious rituals that are carried out routinely. Islamic society, both traditions are products of acculturation and cultural assimilation. This study is a library research using a critical historical approach. Historical methods are used for the process of examining and critically analyzing past records and relics. From a historical perspective, the manaqib genre is a genre that was developed from the perspective of the tradition of writing Islamic history and oral traditions that form the culture of manaqiban in the culture of Islamic society. From the content aspect, it consists of good moral values ​​(akhlaq) that can inspire and become a reference for building a nation's character based on Islamic culture in the modern era. From the aspect of implementing cultural preservation, it will have a positive impact on building morality. From the aspect of writing, the Book of Manaqib al-Busyra is the work of a scholar as an educator and sirah (historical) expert who can be accounted for by the moral mission and references of a manaqib.